PENGARUH ROA, ROE, NPM DAN CR TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) - ARYANTI ARYANTI; MAWARDI MAWARDI (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2016)
The purpose of this research is to determine the influence of the company's performance using Independent Variables ROA, ROE, NPM and CR to Stock Return. This research uses Eviews Application 7. Results showed that Partially ROE and CR has negative effect and significant to Stock Return, ROA has positive effect and not significant to Stock Return and NPM has no effect and significant to Stock Return. While simultaneously that ROA, ROE, NPM and CR have effect on Stock Return. The coefficient of determination (R ²) based on the output display eviews7 show that the value of Adjusted R2 of Stock Return is 0.910907. It means that 91.09% the variation is explained by the variation of the four independent variables ROA, ROE, CR and NPM. While the rest of 8.91% is explained by other causes outside the model.Key word: Return On Assets, Return On Equity, Net Profit Margin, Current Ratio, Return Saham, Jakarta Islamic Index